Ovarian cancer treatment and natural killer cell-based immunotherapy - Fan, Zhongru; Han, Dongyu; Fan, Xin; Zhao, Lin (Frontiers in Immunology, 2023)
Background: Ovarian cancer (OC) is one of the malignant tumours that poses a serious threat to women's health. Natural killer (NK) cells are an integral part of the immune system and have the ability to kill tumour cells directly or participate indirectly in the anti-tumour immune response. In recent years, NK cell-based immunotherapy for OC has shown remarkable potential. However, its mechanisms and effects remain unclear when compared to standard treatment.To explore the value of NK cell-based immunotherapy in the treatment of OC, we conducted a literature review.In comparison to standard treatment, our focus was primarily on the current anti-tumour mechanisms, the clinical effect of NK cells against OC, factors affecting the structure and function of NK cells, and strategies to enhance the effectiveness of NK cells.We found that NK cells exert their therapeutic effects in OC through mechanisms such as antibody-dependent cell cytotoxicity, perforin release, and granule enzyme secretion. They also secrete IFN-γ and TNF-α or engage in Fas/FasL and TRAIL/TRAILR pathways, mediating the death of OC cells. In clinical trials, the majority of patients experienced disease stability with mild side effects after receiving NK cell-based immunotherapy, but there is still a lack of high-quality research evidence regarding its clinical effectiveness. OC and prior experience with standard treatments have an effect on NK cells, and it may be considered to maximize NK cell effects through the modulation of the tumour microenvironment or combination with other therapies.In this review, we have summarized the current evidence of NK cell applications in the treatment of OC.Furthermore, factors and strategies that influence and enhance the role of NK cell immunotherapy are discussed.